Para-badminton: technical and temporal characteristics - Strapasson, Aline Miranda (2018)
The aim of this study was to characterize and compare technical and temporal characteristics of PBd matches in WH1 and WH2 classes (WH - wheelchair) through the scout. A descriptive study was carried out with inferential analysis for comparison between groups. Six PBd matches (WH1/WH2 classes, men single) were filmed and analyzed during a World Championship. The temporal and technical variables were analyzed. The results show that: total time of WH1 and WH2 categories did not present significant statistical differences and WH2 class rally time is higher than the pause time, characterizing greater intensity of the game. The items that presented significant statistical differences among the categories were: rest time, strokes frequency, game density, rally strokes. As for the strokes executed, the only one that presented significant difference was drive, the least used stroke in the games. The most used strokes were clear, lob, drop and net-shot; and the number of non-forced errors were greater than winning points. The conclusion is that is possible to characterize and compare technical and temporal characteristics of PBd games using scout as a game analysis tool.